Activation of Prp28 ATPase by phosphorylated Npl3 at a critical step of spliceosome remodeling - Yeh, Fu-Lung; Chang, Shang-Lin; Ahmed, Golam Rizvee; Liu, Hsin-I; Tung, Luh; Yeh, Chung-Shu; Lanier, Leah Stands; Maeder, Corina; Lin, Che-Min; Tsai, Shu-Chun; Hsiao, Wan-Yi; Chang, Wei-Hau; et al. (Nature communications, 2021)
Splicing, a key step in the eukaryotic gene-expression pathway, converts precursor messenger RNA (pre-mRNA) into mRNA by excising introns and ligating exons. This task is accomplished by the spliceosome, a macromolecular machine that must undergo sequential conformational changes to establish its active site. Each of these major changes requires a dedicated DExD/H-box ATPase, but how these enzymes are activated remain obscure. Here we show that Prp28, a yeast DEAD-box ATPase, transiently interacts with the conserved 5′ splice-site (5′SS) GU dinucleotide and makes splicing-dependent contacts with the U1 snRNP protein U1C, and U4/U6.U5 tri-snRNP proteins, Prp8, Brr2, and Snu114. We further show that Prp28’s ATPase activity is potentiated by the phosphorylated Npl3, but not the unphosphorylated Npl3, thus suggesting a strategy for regulating DExD/H-box ATPases. We propose that Npl3 is a functional counterpart of the metazoan-specific Prp28 N-terminal region, which can be phosphorylated and serves as an anchor to human spliceosome. Yeast helicase Prp28 promotes the first step of spliceosome remodeling. By placing a photoactivatable unnatural amino acid in Prp28, the authors capture Prp28 in action revealing its dynamic interactions and cofactor Npl3.